Reproductive health and development in spaceflight environments - Byeonggyu Ahn; Jina Ha; Dawon Kang (Journal of Animal Reproduction and Biotechnology)
As space missions extend in duration, the impact of spaceflight on human reproduction poses serious biomedical challenges. The reproductive system is susceptible to microgravity, ionizing radiation, and circadian disruption. This review summarizes current evidence on how space environments affect reproductive function, focusing on gametogenesis, hormonal regulation, pregnancy, and embryonic development. We reviewed data from rodent models, parabolic flight experiments, and space-exposed cellular systems to assess the effect of space-relevant stressors on reproductive health. Findings show that microgravity impairs sperm motility and hormonal balance, while radiation increases DNA fragmentation and induces heritable epigenetic changes. Female reproductive health is similarly affected, with radiation accelerating follicular loss and hormonal disruption impairing ovulation. Early pregnancy stages, including implantation and placental development, are especially vulnerable to space conditions. Rodent studies indicate that while basic fertility may persist, the long-term effect on offspring health and multi-generational outcomes remains unclear. These findings highlight the need for targeted countermeasures and continued research to ensure reproductive success in future space missions.